Molecular Detection of Multi-drug Resistant Tuberculosis in Clinical Isolates from Two Urban Centres in Malawi - Sikwese, Tionge; Msosa, Takondwa; Twabi, Hussein; Dzunda, Samuel; Chaima, David; Banda, Billy; Kanamazina, Yusuf; Nyenje, Mirriam; Musopole, Alinune; Nliwasa, Marriott; Ndhlovu., Victor (Archives of Clinical and Biomedical Research, 2025)
Introduction: Suboptimal chemotherapy allows Mycobacterium tuberculosis to develop drug resistance owing to development of resistant mutants in the mycobacterial population. Early diagnosis of TB and identification of drugresistance is of particular importance in human immunodeficiency virus (HIV)-infected individuals, as delay of therapy and subsequent development of drug-resistant TB can be devastating due to compromised immune systems. Methodology: We conducted a cross-sectional evaluation study using presumptive M. tuberculosis positive clinical isolates at two urban sites in Malawi (Blantyre and Lilongwe) to assess the presence of mutant genes on first and second line TB drugs using Line Probe Assay (LPA) and the gold standard drug susceptibility test (DST). Results: For the Lilongwe site, the incidence of MDR-TB by Line Probe Assay (LPA) was found to be 14.06% (95% CI: 8%-20%) whereas that for Rif mono-resistance was 6.25% (95% CI: 2%-10%). Contrastingly, MDRTB by DST was 23.44% (95 CI:16% - 21%) while mono-resistance was 6.25% (95% CI:2% -10). There was a substantial agreement on the detection of MDR-TB (kappa statistic was 0.75 with 95% CI of 0.62-0.88). Blantyre site, at 9.5% confidence interval, the point estimate for MDR-TB was 0% while for INH mono-resistance TB was 3.3%. Conclusion: There is high incidence of MDR-TB among patients whose samples are sent to the Lilongwe site than previously thought. A short turnaround time to diagnosis, and the ability to simultaneously detect rifampicin and isoniazid resistance, makes LPA a reliable tool for the early detection of multidrug-resistant tuberculosis.